Pelaksanaan Program Little Chef dalam Upaya Meningkatkan Motivasi Berbicara Bahasa Inggris Siswa KG 1 di Kiddos Preschool - Ni Komang Aprilia Dewi; Luh Made Dwi Wedayanthi (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The little chef program at Kiddos Preschool has succeeded in improving the English speaking skills of KG1 students. Before the program, students were hesitant to speak English, but after joining the program, they showed significant improvements in vocabulary and confidence. On average, students were able to mention 10 new vocabulary words related to cooking and participated more actively in discussions. Cooking activities create a fun learning atmosphere and support active language use. Interviews with students and teachers show that the program not only improves language skills, but also students' self-confidence and social skills. With the right teacher support, this program can continue to evolve to meet student needs.